Understanding Donald Trumps inconsistent foreign policy through psychological assessments: the case of North Korea - Vilas Boas, Vinícius Hyppolito Rodrigues (2023)
This thesis is dedicated to an analysis of the Trump administrations foreign policy, which is widely understood as inconsistent and incoherent. In order to understand these characteristics, I hypothesize that the Trump administrations foreign policy was inconsistent and incoherent because it was deeply influenced by the presidents personality. To build this analysis, I first outline the absence of a Trump Grand Strategy or a Trump Doctrine, or any type of guiding principle that could comprehensively explain the Trump administrations foreign policy. Out of the few distinguishable patterns in Trumps international behavior, this thesis explores his populist approach and his centralization of decision-making processes, strengthening the argument that Trumps personal traits might have played an important role in his foreign policy. To test the outlined hypothesis, I draw on Leadership Trait Analysis assumptions and methods, assessing Trumps personality through at-a-distance content analysis. Drawing on the literature on leadership styles, I draw hypotheses about Trumps foreign policy decision-making behavior from his personal traits and compare these with his actual behavior regarding North Korea, which was the selected case for analysis. Results show that the hypotheses drawn from Trumps personality are consistent with his actual foreign policy behavior in U.S diplomacy towards North Korea, which allows us to understand Trumps personal characteristics as causal mechanisms in his decision-making process in this case. In that sense, the inconsistency and incoherence of his foreign policy could be understood as the result of a sum of foreign policy issues that were not strongly defined by ideology or strategy, but were highly influenced by the presidents personal characteristics.